Role of cyclins D1 and D3 in vestibular schwannoma. (13th July 2015) - Jabbour, J; Earls, P; Biggs, N; Gracie, G; Fagan, P; Bova, R
Abstract: Background: Vestibular schwannomas in younger patients have been observed to be larger in size and grow more quickly. Objective: This study aimed to evaluate the expression of three important cell cycle proteins, cyclin D1, cyclin D3 and Ki-67, in vestibular schwannoma patients separated into two age groups: ≤40 years or >40 years. Method: Immunohistochemical detection of cyclin D1, cyclin D3 and Ki-67 was undertaken in 180 surgically resected vestibular schwannomas. Results: The proliferation index of vestibular schwannomas was statistically higher in the ≤40 years age group compared to that in the >40 years age group (mean of 4.52 vs 3.27, respectively; p = 0.01). Overexpression of cyclin D1 and cyclin D3 was found in 68 per cent and 44 per cent of tumours, respectively. Conclusion: There was an increased Ki-67 proliferation index in the younger age group that appears to correlate with clinical behaviour. Vestibular schwannomas in both age groups show increased expression of cyclin D1 and cyclin D3 .